Effects of electron irradiation on structure and bonding of SF₆ on Ru(0001) - Faradzhev, N.S.; Kusmierek, D.O.; Yakshinskiy, B.V.; Madey, T.E. (Физика низких температур, 2003)
Electron stimulated desorption ion angular distribution (ESDIAD) and temperature programmed desorption (TPD) techniques have been employed to study radiation-induced decomposition of fractional monolayer SF₆ films physisorbed on Ru(0001) at 25 K. Our focus is on the origin of F⁺ and F⁻ ions, which dominate ESD from fractional monolayers. F⁻ ions escape only in off-normal directions and originate from undissociated molecules. The origins of F⁺ ions are more complicated. The F⁺ ions from electron stimulated desorption of molecularly adsorbed SF₆ desorb in off-normal directions, in symmetric ESDIAD patterns. Electron beam exposure leads to formation of SFx (x = 0 - 5) fragments, which become the source of positive ions in normal and off-normal directions. Electron exposure > 10¹⁶ cm⁻ ² results in decomposition of the entire adsorbed SF₆ layer.